Optimal Distribution Systems Expansion Planning for Improving Service Restoration - Macedo, Leonardo H. [UNESP]; Ortega-Vazquez, Miguel A.; Romero, Ruben [UNESP]; IEEE (Ieee, 2018)
This paper presents a mixed-integer second order cone programming model for the problem of optimal distribution systems expansion planning for improving service restoration. The objective is to obtain a network that allows the load to be restored after the occurrence of a contingency. Expansion of new substations, reinforcement of existing ones, addition and reconductoring of feeders are considered in the formulation of this problem. The objective is to find a meshed network that minimizes expansion costs, as well as the radial topologies for operation in predefined contingency scenarios that minimize the energy not supplied. The model considers the full ac power flow equations for the operation of the system. A 24-node network is used to demonstrate the effectiveness of the proposed method. A comparison of the costs of the traditional planning with the costs of planning considering service restoration is carried out.
Keywords: Distribution systems expansion planning; mixed-integer second order cone programming; service restoration